2017
DOI: 10.1038/srep40441
|View full text |Cite
|
Sign up to set email alerts
|

An electromagnetic modulator based on electrically controllable metamaterial analogue to electromagnetically induced transparency

Abstract: Electromagnetically induced transparency (EIT) is a promising technology for the enhancement of light-matter interactions, and recent demonstrations of the EIT analogue realized in artificial micro-structured medium have remarkably reduced the extreme requirement for experimental observation of EIT spectrum. In this paper, we propose to electrically control the EIT-like spectrum in a metamaterial as an electromagnetic modulator. A diode acting as a tunable resistor is loaded in the gap of paired wires to induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
57
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(58 citation statements)
references
References 48 publications
0
57
1
Order By: Relevance
“…Also, we have shown that HRTEM can further provide information about particle size distribution and lattice fringe of the carbon nanotubes and related catalysts [77][78][79][80][81][82][83][84][85][86][87][88][89]. The controllable synthesis of carbon nanotubes with tailored properties is certainly a challenge for researchers thanks to their valuable applications in several fields.…”
Section: Introductionmentioning
confidence: 99%
“…Also, we have shown that HRTEM can further provide information about particle size distribution and lattice fringe of the carbon nanotubes and related catalysts [77][78][79][80][81][82][83][84][85][86][87][88][89]. The controllable synthesis of carbon nanotubes with tailored properties is certainly a challenge for researchers thanks to their valuable applications in several fields.…”
Section: Introductionmentioning
confidence: 99%
“…Terahertz bandpass devices, such as the THz modulators and sensing devices [14], have been developed by applying the transparency window of the EIT. Recently, in order to achieve more transparent window, many studies have been carried out to optimize the EIT effect by adapting the analysis mode [13], coupling [15][16][17][18][19][20][21], absorption [22][23][24][25][26][27], and active tuning [28][29][30]. Gu et al observed the excitation and tuning of EIT by the interference between different excitation pathways of the dark mode in a planar terahertz metamaterial [10].…”
Section: Introductionmentioning
confidence: 99%
“…The PIT effect has been observed in different structures, such as hybrid metal-graphene metasurfaces [11][12][13][14][15], integrated photonics [16], metallic nanoparticles [17,18], wave-guide systems [19,20], and plasmonic coupled cavities [21,22]. The metasurfaces [23][24][25][26][27][28] can be tuned electrically [29][30][31][32][33][34][35][36], thermally [37], and mechanically [38].…”
Section: Introductionmentioning
confidence: 99%